Transformation of Qur'an and Hadith Learning Through Merdeka Curriculum in Indonesia - Salmiarti, Rahma; Zahra, Madinatul; Risky, Widya Alfa; Sabri, Ahmad; Hidayatullah, Rully (IDRIS Darulfunun Institute, 2024)
This research uses qualitative methods to investigate the transformation of Qur'anic and Hadith learning in Indonesia through the implementation of Merdeka Curriculum. The focus of the research includes the identification of barriers in traditional religious education, an emphasis on the need for a more dynamic and inclusive teaching approach to these key texts, as well as an explanation of solutions involving the adoption of Merdeka Curriculum. The curriculum incorporates innovative teaching methods, technology and community participation. The results show that traditional religious education in Indonesia is faced with a number of challenges, including monotonous teaching methods, lack of student interaction, and less relevance to contemporary life. Therefore, a more dynamic and inclusive teaching approach is needed to arouse students' interest and understanding of the Qur'an and Hadith. Merdeka Curriculum is considered a promising solution by bringing together innovative teaching methods, technology and community engagement. Its implementation showed significant improvements in student engagement, understanding, and application of the teachings of the Qur'an and Hadith. In conclusion, curriculum reform through Merdeka Curriculum has an important role to play in strengthening the understanding and appreciation of Islamic principles among students in Indonesia. This more dynamic and inclusive approach can help the younger generation to understand and appreciate the principles of Islam.